A systematic review of the literature relating to captive great ape morbidity and mortality - Strong, Victoria J.; Grindlay, Douglas J.C.; Redrobe, Sharon; Cobb, Malcolm; White, Kate (American Association of Zoo Veterinarians, 2016)
Wild bonobos (Pan paniscus), chimpanzees (Pan troglodytes), Western gorillas (Gorilla gorilla), and orangutans (Pongo pygmaeus, Pongo abelii) are threatened with extinction. In order to help maintain a self-sustaining zoo population, clinicians require a sound understanding of the diseases with which they might be presented. To provide an up-to-date perspective on great ape morbidity and mortality, a systematic review of the zoological and veterinary literature of great apes from 1990 to 2014 was conducted. This is the first review of the great ape literature published since 1990 and the first-ever systematic literature review of great ape morbidity and mortality. The following databases were searched for relevant articles: CAB Abstracts, Web of Science Core Collection, BIOSIS Citation Index, BIOSIS Previews, Current Contents Connect, Data Citation Index, Derwent Innovations Index, MEDLINE, SciELO Citation Index, and Zoological Record. A total of 189 articles reporting on the causes of morbidity and mortality among captive great apes were selected and divided into comparative morbidity–mortality studies and case reports–series or single-disease prevalence studies. The content and main findings of the morbidity-mortality studies were reviewed and the main limitations identified. The case reports–case series and single-disease prevalence studies were categorized and coded according to taxa, etiology, and body system. Subsequent analysis allowed the amount of literature coverage afforded to each category to be calculated and the main diseases and disorders reported within the literature to be identified. This review concludes that reports of idiopathic and infectious diseases along with disorders of the cardiovascular, respiratory, and gastrointestinal body systems were particularly prominent within the great ape literature during 1990–2014. However, recent and accurate prevalence figures are lacking and there are flaws in those reviews that do exist. There is therefore a critical need for a robust, widespread, and more up-to-date review of mortality among captive great apes.